The interplay between the REDD+ mechanism and forest-related institutions in Indonesia - Mulyani, M; Mari E. Mulyani (2014)
A policy mechanism known as REDD+ (‘Reducing Emissions from Deforestation and forest Degradation, and enhancing forest carbon stocks and conservation’) is designed to contribute to climate change mitigation efforts and simultaneously support developing countries’ national development agendas. This is effected by providing REDD+ host countries with financial incentives to produce measurable reductions in carbon emissions beyond what would have occurred without REDD+. Indonesia is a key target of the REDD+ mechanism for several reasons, eg: (i) its forests support 10% of the world's remaining tropical rain forests and represent the fourth largest forest carbon stock globally, (ii) 80% of its GHG emissions result from deforestation and forest degradation, and (iii) it has the potential to reduce up to 120 million tons of CO2 per year. Consequently, to date Indonesia has received donor’s commitments of nearly US$2 billion for REDD+ development. Given this profile, Indonesia’s success in implementing REDD+ can contribute significantly to the efficacy of REDD+ globally. However, achieving this potential is undermined by a set of long-standing problems inherent within Indonesia’s forest institutions, including issues of corruption, coordination, uncertainty in the forests’ legal system, capacity to manage forests at multiple levels of government, and the use of forest concessions to consolidate political power. This thesis asks the primary research question: “How do REDD+ institutions effect governance reform within Indonesia’s existing national and sub-national forest institutions?” 'Institutionalism', in particular the concept of 'institutional interplay' is the main conceptual framework deployed and grounded in the context of the vertical interplay between the internationally-formulated REDD+ mechanism and Indonesia's forest institutions. Guided by the themes that emerged from the data collected, this research explored and expanded certain analytical approaches within the perspectives of institutionalism and governance, namely ‘historical institutionalism’, ‘clientelism’, 'critical juncture', ‘policy networks’ and ‘social learning’. This thesis adopted the ‘four paper route’ and employed mixed methods of data collection (ie interview, shadowing, and policy document review). It found that during the process of institutional interplay as REDD+ institutions deployed the principles of good governance, advanced a robust system of measurement, reporting and verification of reductions in carbon emission, attracted large funding, and involved a broad range and multi-scale of actors, the REDD+ mechanism produced 'collateral benefits'. The tangible form of these benefits was the production of new policy instruments, eg the 'national REDD+ strategy' (paper 2), 'one map initiative' (paper 3), and ‘village agreement’ (paper 4) through which a significant body of evidence showed the capability of REDD+ to effect governance reform within and beyond Indonesia's forestry sector. Paper 1, revealed how policy actors perceived REDD+ and as such provides the basis of these three papers. The positive results of institutional interplay that occurred were determined not only by the characteristic of REDD+ institutions themselves but also by the existence of domestic reformists and the national reform agenda.